Scientific approach in developing mathematical analogy and communication ability of junior high school students in remote areas - H Hendriana; H D Putra; M G Ristiana (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to determine the ability of mathematical analogies and communication ability of students in remote areas through a scientific approach. The research method is quantitative with pretest and posttest design in the experimental class. The subjects were 117 students consisting of 29 students of class VII, as many as 43 students of class VIII, and as many as 45 students of class IX. The results showed that through the scientific approach, the mathematical analogy ability of grade VII students increased with the low category, while class VIII and IX increased by medium category. Mathematical communication ability of grade VII and VIII students increased with the high category, and class IX increased with the medium category. Students are actively involved in observing problems, asking questions, trying strategies, solving problems, and concluding concepts. Students are good at getting involved to help less-clever students. Students in remote schools have the potential to develop analogy and mathematical communication skills.